2012
DOI: 10.1161/circheartfailure.112.967695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Blocker Cessation on Chronotropic Incompetence and Exercise Tolerance in Patients With Advanced Heart Failure

Abstract: All patients with systolic HF, New York Heart Association class II to IV, receiving β-blocker therapy (bisoprolol, carvedilol, or metoprolol) for ≥3 months referred for cardiopulmonary exercise tolerance testing (CPETT) were screened. All patients were followed at the Columbia © 2012 American Heart Association, Inc. Background-Chronotropic incompetence is defined as the inability to reach 80% of heart rate (HR) reserve or 80% of the maximally predicted HR during exercise. The presence of chronotropic incompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…The above‐mentioned interdependency, together with the prognostic role of pVO 2 in HF patients, often raised the question about the actual independent value of exercise‐induced HR response in cardiovascular mortality stratification . Moreover, it is well known that beta‐blocker treatment might per se contribute to reduce most of the chronotropic indices even if it does not significantly affect pVO 2 values , . To our knowledge, only two studies investigated a possible significance of CI together with CPET data .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above‐mentioned interdependency, together with the prognostic role of pVO 2 in HF patients, often raised the question about the actual independent value of exercise‐induced HR response in cardiovascular mortality stratification . Moreover, it is well known that beta‐blocker treatment might per se contribute to reduce most of the chronotropic indices even if it does not significantly affect pVO 2 values , . To our knowledge, only two studies investigated a possible significance of CI together with CPET data .…”
Section: Discussionmentioning
confidence: 99%
“…11,16 Moreover, it is well known that betablocker treatment might per se contribute to reduce most of the chronotropic indices 11,21 -23 even if it does not significantly affect pVO 2 values. 23,41,42 To our knowledge, only two studies investigated a possible significance of CI together with CPET data. 11,16 Bold characters identify the best multivariate coefficient for %pHR and %pHRR cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…This complication arises from frequent/chronic activation of sympathetic nerves, which leads to down-regulation of b-adrenergic receptors in the sinus node. This ultimately results in post-synaptic desensitization [63][64][65][66]. As the HR response to exercise is determined by the extent of sympathetic drive to the heart and the ability of b-adrenergic receptors in the sinoatrial node to respond to circulating catecholamines, such desensitization could then result in a disturbed HR regulation/ response during exercise [64,67].…”
Section: Cardiovascular Autonomic Neuropathymentioning
confidence: 99%
“…Although it has been shown that high doses of beta-blockers can cause, aggravate, or reveal latent chronotropic incompetence, 7 26 27 beta-blocker cessation did not normalize chronotropic response to exercise. 28 Our study has some limitations as this was a single-center, observational, retrospective study with a relatively small group of mostly male patients. It included a diverse group of patients with and without heart failure.…”
Section: Discussionmentioning
confidence: 93%